Let f(x)=x^2+3 and g(x)=2x-7. Find and simplify each expression :(f-g)(-2). Also find g(a+2)

so

(f - g)(x)= (x² + 3) - (2x - 7) = x² - 2x + 10

for x = - 2

so : (f - g)(- 2) = 4 + 4 +10 = 18

and

g(a + 2)= 2 (a + 2) - 7 = 2a + 4 - 7 = 2a - 3

GOOD LUCK

please if you have an other homework call me first i will give you the best answer

Okay I will.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up